Secondary metabolites and pharmacological potential of Thuja orientalis and T. occidentalis: A short review - Tech, Maria Eduarda; Magalhães, Cássia Gonçalves; Vieira Filho, Sidney Augusto (Eclética Química, 2022)
Species from Thuja genus (Cupressaceae) are found in Brazil, North America and Asia. In the traditional medicine, these plants are used in the treatment of cough, skin allergies, and asthma. In Brazil, Thuja species are also used in the ornamentation of urban areas. Different parts of these plants displayed insecticidal, antitumor, and antioxidant activities. The essential oil of the leaves from Thuja spp. are constituted by monoterpenes and sesquiterpenes. The main substances found in the extracts of these species are flavonoids, which display relevant biological activities. This brief review shows recent phytochemical studies involving T. orientalis and T. occidentalis, as well as 40 constituents isolated from these species. The existing pharmacological potential justifies the growing scientific interest in this genus.